Pertanggungjawaban Pidana Pejabat Pembuat Komitmen Akibat Terjadinya Kerugian Keuangan Negara Dalam Pengadaan Barang/Jasa Pemerintah - Dina Karlina Amri Lubis; Alvi Syahrin; Budiman Ginting; Hasim Purba (USU LAW JOURNAL, 2019)
Abstract.Government procurement has a positive impact on the economy and national development, but the success of procurement in moving the national economy has always been the Foundation of the land deeds of criminal acts of corruption that contribute cause a loss of the country. Official Commitment Maker as executing the budget and one of the principals of procurement faced with responsibility over any Government-issued rupiah to get the right goods and services (value for money).  Seen from the aspect of the law, legal risk in government procurement have three (3) legal systems, namely, administrative law, civil law, and criminal law. Not understanding law enforcement officers against the third character of the legal system that works in the procurement, implies the occurrence of errors in the application of the law, in particular the application of the law of criminal corruption in the event of the occurrence of financial loss State and potentially tofor review by law enforcement officials, made witnesses, even defined as a criminal act corruption suspects. The condition, causing the onset of apathy from the perpetrator, with procurement were not willing to be appointed as procurement, specifically designated as Official Commitment Maker. As for, the problems raised in the research thesis, first: how the criminal law aspects of Corruption in Government procurement of goods/services, these two: how the Criminal Liability of officials due to the occurrence of Commitment Makers financial losses The country in Government procurement of goods/services, and third: How legal protection of officials of financial Losses due to Commitment Makers State in Government procurement of goods/services. Fulfillment of responsibility in government procurement could be distinguished in two forms, namely the responsibility of Office and criminal liability. Criminal liability is the parameter elements of tort law (wederrechtelijk) and abuse of authority based upon the nature of the error on purpose (dolus) and neglect (culpa), when these elements are met, then the Act of conducted by Officials have met the commitment maker indications of corruption in article 2 and 3 of Act No. 20 of 2001 changes to the Act No. 31 of the year 1999 about the eradication of criminal acts of corruption, so that personal accountability leads to criminal liability.   Keywords: governmentprocurement, criminal liability, state officials PPK